A first assessment of sea lice abundance in Arnarfjörður, Iceland : sentinel cage sampling and assessment of hydrodynamic modelling feasibility - Karbowski, Chelsey Mae, 1991- (2015)
Verkefnið er lokað til 30.6.2017. Two sea lice species are of significant concern for both aquaculture and wild salmonids in the North Atlantic, C. elongatus (von Nordmann 1832) and L. salmonis (Krøyer, 1837). Research has typically focused on the impacts from L. salmonis, as they are the most threatening for salmonid aquaculture causing epidemics in various countries such as Canada, Scotland and Norway. The focus of research has been to assess the abundance of sea lice to determine the threat of epidemics, need for treatment and management. This study used sentinel cages for sampling the abundance of sea lice in Arnarfjördur, Iceland in June, July and August. Results were used to provide a baseline data set; which is valuable for Iceland providing an idea of the lice abundance, before high levels of aquaculture production has developed. Sampling sea lice abundance and management is increasingly connected to hydrodynamic modelling, predicting the dispersal of sea lice in surface currents. This study also assessed the feasibility of hydrodynamic modelling in Arnarfjördur, in connection to the baseline sentinel cage and gill-netting data. Results from this study suggested two areas with significant lice abundance, representative of the sites closest to the aquaculture farms. This suggested an influence from aquaculture farms, but cannot be confirmed due to conflicting results from other sites. Hydrodynamic modelling feasibility is not restricted by the availability of data but by the cost of accessing it. Feasibility should increase with a increase in the threat of lice epidemics. In the future a comprehensive integrated management approach should be used.